2020
DOI: 10.1088/2058-6272/ab6487
|View full text |Cite
|
Sign up to set email alerts
|

The far-field plasma characterization in a 600 W Hall thruster plume by laser-induced fluorescence

Abstract: Non-intrusive characterization of the singly ionized xenon velocity in Hall thruster plume using laser induced fluorescence (LIF) is critical for constructing a complete picture of plume plasma, deeply understanding the ion dynamics in the plume, and providing validation data for numerical simulation. This work presents LIF measurements of singly ionized xenon axial velocity on a grid ranging from 100 to 300 mm in axial direction and from 0 to 50 mm in radial direction for a 600 W Hall thruster operating at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Multimodal iVDF is not a novelty and is often mentioned in the literature. For example, in [85] using the LIF method, it was found that a multi-peaked iVDF is present at the outer radius of the plume even at a great distance from the thruster. In [86][87][88], LIF measurements of the iVDF were carried out near the channel, depending on the time.…”
Section: Virtual Cathode and Ivdf Effectsmentioning
confidence: 99%
“…Multimodal iVDF is not a novelty and is often mentioned in the literature. For example, in [85] using the LIF method, it was found that a multi-peaked iVDF is present at the outer radius of the plume even at a great distance from the thruster. In [86][87][88], LIF measurements of the iVDF were carried out near the channel, depending on the time.…”
Section: Virtual Cathode and Ivdf Effectsmentioning
confidence: 99%
“…One way to accurately determine the zero-Doppler shift excitation wavelength is to send a laser in both forward and backward directions of the diagnosed volume and compare the resultant fluorescence spectrum, this eliminates potential particle drift within the diagnosed volume [61,63]. Alternatively, optogalvanic cells are also used to obtain absolute wavelength calibration, and they are often better than iodine in the sense that an optogalvanic cell can give the exact same line as the target fluorescence line if one chose the same gas as the one being probed [16,17,64,65]. However, by nature of the optogalvanic cell being a plasma source, there is also no guarantee that the ion VDF in the cell is free of any drift velocity, particularly when they are generally very small device without any form of confinement to ensure plasma uniformity.…”
Section: Accurate Determination Of Exact Laser Wavelengthsmentioning
confidence: 99%
“…LIF technique had been used to measure the IVDFs of Xe + ions in the plasma of several Hall thrusters and in Hall thruster plumes [16][17][18][19][20][21]. For instance, the far-field plasma characteristics of ion VDF and plasma ion temperature in 600 W magnetic shield and unshielded Hall thrusters are studied in [65,150]. An LIF optical bench along with the methodology is extensively described in [21].…”
Section: Hall-effect Thrustersmentioning
confidence: 99%
“…Matthew Baird et al obtained a quiescent sinusoidal discharge current in only the low flow and voltage operation condition [12]. Duan X Y et al investigated the far-field plasma characterization in a 600W Hall thruster [13]. Ding Y J et al found the point of intersection of the characteristic magnetic field line with the channel wall affected the performance and lifetime of the low power cylindrical Hall thruster [14].…”
Section: Introductionmentioning
confidence: 99%